Determining International Joint Venture Performance: The Role of Factors at the Pre-Formation and Post-Formation Stages of the International Joint Venture - Hietala, Riku Mikael (My University, 2025)
This thesis examines the determinants of international joint venture (IJV) performance by adopting a lifecycle perspective that integrates both pre-formation and post-formation stages. It addresses a common limitation in literature, where these phases are frequently analyzed in isolation, thereby overlooking their interdependent effects on IJV outcomes. Based on a conceptual framework grounded in prior research, the study considers strategic, structural, and relational determinants, including partner reputation, prior collaborative experience, firm size, host country risk, inter-partner trust, communication quality, cultural adaptation, ownership structure, and conducts interview with a senior executive from a Finnish manufacturing company with responsibility for three IJVs located in Poland, China, and Finland. All joint ventures had been newly established legal entities and differed in ownership structures and partner histories. The findings indicate that favorable pre-formation conditions, such as prior collaborative experience and partner reputation did not consistently translate into positive relational outcomes. Pre-formation factors such as partner reputation, prior collaboration, equity structure, firm size and resource complementarity did not consistently explain IJV performance. Instead, host country risk had effect. Post-formation factors like trust and cultural adaptation were relevant drivers of performance. This study contributes to international business literature by advancing an empirically grounded, dynamic understanding of IJV success and by proposing nine theoretical propositions and a lifecycle-based framework illustrating how multiple factors interact to influence IJV performance.
Keywords: joint ventures; determinants; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business